Peningkatan Hasil Belajar Pai Menggunakan Model TPACK (Technological Pedagogical Content Knowledge) Siswa Kelas VIII di SMPN 2 Kecamatan Payakumbuh - Yessi Gusman; Zulfani Sesmiarni; Rodi Rodi; Meyriza Hamda (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research is motivated by the low learning outcomes of Islamic Religious Education students at SMPN 2 Payakumbuh District. Video media through the TPACK learning model is the most appropriate and accurate learning media in conveying messages and will greatly help students' understanding. The purpose of this study was to: determine the improvement of students' Islamic Religious Education (PAI) learning outcomes through the TPACK learning model at UPTD SMPN 2 Payakumbuh District. The data collection techniques used were tests and observations. The results showed that video media in PAI subjects was able to increase student learning motivation, especially class VIII students at UPTD SMPN 2 Payakumbuh District. Quantitative evidence can be seen an increase in the test of motivation variables from the first meeting and the second meeting. From the test results also increased from pre-action results of 45%, in cycle I (first) increased to 60%, in cycle II (second) also increased to 90%. While qualitative evidence is that it can be explained from the number of students who expressed pleasure in the use of this TPACK model of growing motivation, student concentration in PAI subjects.